Complex facial emotion recognition and atypical gaze patterns in autistic adults - Black, Melissa; Chen, Nigel T.M.; Lipp, Ottmar; Bolte, Sven; Girdler, Sonya (SAGE PUBLICATIONS LTD, 2020)
While altered gaze behaviour during facial emotion recognition has been observed in autistic individuals, there remains marked inconsistency in findings, with the majority of previous research focused towards the processing of basic emotional expressions. There is a need to examine whether atypical gaze during facial emotion recognition extends to more complex emotional expressions, which are experienced as part of everyday social functioning. The eye gaze of 20 autistic and 20 IQ-matched neurotypical adults was examined during a facial emotion recognition task of complex, dynamic emotion displays. Autistic adults fixated longer on the mouth region when viewing complex emotions compared to neurotypical adults, indicating that altered prioritization of visual information may contribute to facial emotion recognition impairment. Results confirm the need for more ecologically valid stimuli for the elucidation of the mechanisms underlying facial emotion recognition difficulty in autistic individuals.